Revealing the Disturbed Vaginal Micobiota Caused by Cervical Cancer Using High-Throughput Sequencing Technology - Xie, Yupei; Feng, Ying; Li, Wenyu; Zhan, Fuliang; Huang, Genhua; Hu, Hui; Xiong, Yifei; Tan, Buzhen; Chen, Tingtao (Frontiers in Cellular and Infection Microbiology, 2020)
Cervical cancer is the fourth most prevalent cancer type among all malignancies, therefore finding its actual pathogenesis mechanisms is of great significance. In the present study, 90 women were enrolled, and high-throughput sequencing technology was firstly used to analyse the vaginal microbiota of healthy women (C group), cervical intraepithelial neoplasia patients (CIN group) and cervical cancer patients (CER group). Our results indicates that compared to C group, a higher HPV infection rate as well as increased Neutrophil ratio and tumor marker SCCA were obtained, and a decrease in Lymphocyte ratio and Hemoglobin were also present. In addition, the cervical cancer showed a strong association with reduced probiotics Lactobacillus, and increased pathogens Prevotella spp., Sneathia spp. and Pseudomonas spp.. The results prove that the disturbed vaginal microbiota is closely linked to cervical cancer; however, further study investigating the key bacteria for cervical cancer is still needed, which can be a clue for the diagnosis or treatment of cervical cancer.